Bioimaging of nanoparticles: the crucial role of discriminating nanoparticles from free probes. Issue 2 (February 2017) - Hu, Xiongwei; Dong, Xiaochun; Lu, Yi; Qi, Jianping; Zhao, Weili; Wu, Wei
Highlights: Exploring the in vivo fate of nanoparticles is emerging as an interesting and important research topic. It is crucial to discriminate signals of integral nanoparticles from free probes. Environment-responsive probes can report the in vivo fate of nanocarriers by smart signal switching. Water-sensitive fluorescent probes have been used to explore the in vivo fate of lipid nanoparticles. Abstract : The biological fate of nanocarriers has yet to be fully explored, mainly because of the lack of functional tools like probes to identify integral nanocarriers in the body. Understanding their in vivo fate remains as the bottleneck to the development of nanomedicines. Bioimaging results based on conventional fluorescent or radioactive probes should be judged critically because images merely reflect bulk signals of an admixture of the nanoparticles and free probes. It is crucial to discriminate between nanocarrier-bound and free signals. This review analyzes the state-of-the-art of bioimaging of nanoparticles in vivo and highlights directions for future endeavours.